Drawings is a Miracle! Aldo Rossi’s A Scientific Autobiogrhphy (diségno, 2019)
First published under the title A Scientific Autobiography [Rossi 1981a], as part of the Oppositions Books series by the prestigious editors, Peter Eisenman and Kenneth Frampton, translated with great lyrical sensitivity by Lawrence Venuti and commented upon with extraordinary critical acuity by Vincent Scully (author of a memorable afterword entitled Ideology in Form), Aldo Rossi’s A Scientific Autobiography (a story in a personal key to the relationship with architecture and the profession of architect) is an absolutely atypical book, because it manifests itself as a diary, a notebook and a memoir, all at once.